FOOD AS CULTURE: A STUDY ON REGIONAL CUISINE IN THE LATE MEDIEVAL INDIA (International Journal of Food and Nutritional Sciences, 2022)
The regional food culture of medieval India developed dramatically in the eighteenth century with the Mughal decline, when regional powers started dominating the landscape. This fragmentation encouraged the diversity of culinary practices, as regional traditions merged into an expansive Indian cuisine. Food practices, therefore, reveal the socioeconomic and cultural dynamics of Indian society. Each region, informed by indigenous ingredients and techniques, added to the tapestry of flavours and traditions. Such dishes as biryani, jalebi, and khichdi that emerged during this period reflect a cultural synthesis transcending local boundaries. Food, thus, became a marker of social identity, religious practices, and regional customs linking India's historical heritage with its contemporary culinary landscape. This study of regional cuisine illuminates the interplay of cultural, ecological, and political factors that shaped Indian society.